HOW DO CORPORATE SOCIAL RESPONSIBILITY IMPACT ON FINANCIAL PERFORMANCE. Moderate of Ethical Leadership And Firm Size - Tran, Hoang Long; Bui, Van Hung; Tran, Manh Dung; Le, Quoc Hoi; Doan, Xuan Toan; Phan, Thi Thu Hien (CENTRAL ASIA AND THE CAUCASUS, 2021)
The objective of the study is to evaluate the impact of corporate social responsibility on the financial performance of Vietnamese seafood enterprises. Data were analyzed on 689 Vietnamese seafood enterprises, using Smart PLS 3.3 software. The results show that corporate social responsibility has a positive impact on financial performance. At the same time, the mediating variables of customer loyalty, government support, and corporate reputation play a fully mediating role in the relationship between corporate social responsibility and financial performance. Organizational learning has a positive impact on social responsibility and financial performance. Firm size has a moderating role in the relationship between corporate social responsibility and financial performance. The larger the enterprise, the stronger the positive impact of social responsibility on financial performance. In contrast, the smaller the enterprises, the more social responsibility they perform, the worse the financial performance. Finally, ethical leadership has a moderating role in the relationship between social responsibility and corporate reputation. This means, for enterprises with ethical leaders, the more CSR practices, the better corporate reputation. However, for enterprises with a lower ethical leadership style, the more CSR implementation, the more people suspect that the business's reputation is fake.